Soil improvement withsugarcane bagasse ash: technical-economic viabilityfor tertiary roads - Abonía Balanta, Valentina; Serrano Guzmán, Maria Fernanda; Perez Ruiz, Diego Darío (Ingeniería Solidaria, 2024)
Introduction: Economic evaluation of soil subgrade improvement using sugarcane bagasse ash case study: Propal Road - La Cabaña Sugar Mill”, developed at the Pontifical Javeriana University of Cali in 2022.Problem: Tertiary roads in Colombia are essential for mobility in rural areas and for the sugar industry, which generates waste such as sugarcane bagasse ash (SGBA).Objective: To present the results of the economic and technical feasibility study of using sugarcane bagasse ash for soil improvement in tertiary roads.Methodology: Characterization tests of natural soil state and modified Proctor, expansion index, CBR, and unconfined compression for stabilized soils at percentages of 5, 10, 15, and 20% of SGBA are carried out. Results: The mechanical properties of the soil improve with additions of ash between 5% and 15%; however, the utilization of 15% of SGBA is proposed to favor the disposal of a significant volume of this waste.Conclusion: The technical and economic feasibility of using SGBA as a promising solution to improve tertiary roads in Colombia is demonstrated.Originality: Viability of implementing sugarcane bagasse ash on rural roads of sugar mills and agricultural areas with production of this type of waste.Limitations: Similar studies should be carried out for each region to confirm the appropriate percentage for subgrade stabilization using SGBA.